Strategi Go Digital Grow Financial dalam Penguatan Manajemen Keuangan dan Perluasan Pasar UMKM di Desa Sukaraja Kecamatan Rajapolah : Pengabdian - Rachmanda, Yudi Setia; Jayanto, Pery; Darussilmi, Muhamad Alpin; Lutpiah, Silmi; Rahmawati, Suci; Fauzan, Fiqri; Ulum, Aep Saepul; Fauziah, Eva (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Go Digital Grow Financial program, implemented through the Community Service Program (KKN) in Sukaraja Village, Rajapolah District, aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in facing the digital era. MSMEs in this village still encounter several limitations, such as low digital literacy, limited market reach, and weak financial management. The program was carried out in several stages, including observation, training, digital marketing practices, and assistance in simple financial recording based on SAK EMKM. The results showed significant improvements in the ability of MSME actors to utilize e-commerce, create product catalogs, and manage online promotions. In addition, participants began to understand the importance of daily cash recording, separating personal and business finances, and maintaining discipline in cash flow management. This program has proven effective in boosting entrepreneurs’ confidence to expand their markets and establish more transparent financial management. However, challenges remain, particularly technological infrastructure limitations and the need for continuous mentoring.